Barriers and enablers of quality high-acuity neonatal care in sub-Saharan Africa: protocol for a synthesis of qualitative evidence - Abera Mersha; Asresash Demissie; Gugsa Nemera (BMJ Open)
Introduction Neonatal intensive care unit (NICU) in sub-Saharan Africa face limited resources and systemic challenges, resulting in poorer quality care, higher infant mortality, and dissatisfaction among both patients and healthcare workers. This review aims to bridge the knowledge gap by identifying and analysing the key barriers and enablers affecting quality care, informing interventions to improve patient outcomes and overall NICU effectiveness in this critical region.Methods and analysis This systematic review will search and gather data from a variety of databases, including JBI Database, Cochrane Database, MEDLINE/PubMed, CINAHL/EBSCO, EMBASE, PEDro, POPLINE, Proquest, OpenGrey (SIGLE), Google Scholar, Google, APA PsycINFO, Web of Science, Scopus and HINARI. The review will also include unpublished studies and grey literature from a variety of sources. This review will only include qualitative and mixed-methods studies that explore the barriers and enablers of quality care for high-acuity neonates using qualitative data collection and analysis methods. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research will be used by two independent reviewers to critically appraise the eligible studies. Any disagreements that arise will be resolved through discussion. Qualitative research findings will be pooled using the meta-aggregation approach in QARI software, where possible. Only unequivocal and credible findings will be included in the synthesis. If textual pooling is not possible, the findings will be presented in narrative form.Ethics and dissemination This systematic review does not require ethical clearance, and the findings will be disseminated to relevant stakeholders to ensure the widest possible outreach and impact.PROSPERO registration number CRD42023473134.